Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acsami.1c14742
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Fabrication of Nickel–Iron Oxalate Catalysts for Electrochemical Water Oxidation at High Current Densities

Abstract: Ni–Fe-based electrode materials are promising candidates for the oxygen evolution reaction (OER). The synergy between Fe and Ni atoms is crucial in modulating the electronic structure of the active site to enhance electrochemical performance. Herein, a simple chemical immersion technique was used to grow Ni–Fe oxalate nanowires directly on a porous nickel foam substrate. The as-prepared Ni–Fe oxalate electrode exhibited an excellent electrochemical performance of the OER with ultralow overpotentials of 210 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…So far, the state-of-the-art IrO 2 and RuO 2 exhibit the best catalytic OER activity, but their low terrestrial availability and high cost limit their use in large scale applications. [22][23][24] Therefore, signicant research has been directed toward developing earth-abundant transition-metal-based electrocatalysts including oxides, layered double hydroxides (LDH), nitrides, suldes, selenides, and perovskite-based materials. [25][26][27][28][29][30][31][32][33][34] The transition-metal-based catalysts proved to have lower cost, higher natural abundance, unique electronic and mechanical properties, and good OER performances.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the state-of-the-art IrO 2 and RuO 2 exhibit the best catalytic OER activity, but their low terrestrial availability and high cost limit their use in large scale applications. [22][23][24] Therefore, signicant research has been directed toward developing earth-abundant transition-metal-based electrocatalysts including oxides, layered double hydroxides (LDH), nitrides, suldes, selenides, and perovskite-based materials. [25][26][27][28][29][30][31][32][33][34] The transition-metal-based catalysts proved to have lower cost, higher natural abundance, unique electronic and mechanical properties, and good OER performances.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, broad and weak peaks of CoMnFeO 4 result from poor crystallization, high structural disorder, and concentration of active sites. This is possibly beneficial for boosting electrocatalytic performance . In addition, the XRD patterns of CoMnFeO 4 with different Fe contents are also shown in Figure S3a.…”
Section: Resultsmentioning
confidence: 95%
“…The measured potential was calculated according to the reversible hydrogen electrode (RHE) via the following Nernst equation: E RHE = E Ag/AgCl + 0.197 + 0.059pH. The overpotentials were calibrated via the equation: η = E RHE – 1.23 V. The Tafel slopes were obtained from the equation: η = a + b × log j , where “ a ”, “ b ”, and “ j ” represent constant, Tafel slope, and measured current density, respectively. Frequency under the range of 1 × 10 –1 to 1 × 10 5 Hz was carried out during electrochemical impedance spectroscopy (EIS) measurements.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining O 1s XPS spectra with Co 2p XPS spectra as well as Fe 2p XPS spectra, it is concluded that Co-O-Fe interfacial species are generated. Electron migration from Fe to Co along the way of O bridge via the interface could effectively regulate the electronic structure, which in turn optimizes the adsorption and enhances electrochemical behavior of Co-Fe/BP [29,30].…”
Section: Resultsmentioning
confidence: 99%